Assimilation in New Destinations. - Marrow, Helen B. (Tufts University. Tisch Library., 2019)
This article outlines a long-term research agenda on immigrant assimilation by calling on scholars to be more explicit about how we model and measure assimilation, and to move away from previously aspatial approaches to the topic. After briefly overviewing the field, I draw on original qualitative data from a new immigrant destination region to highlight several places where I believe we scholars can better clarify definitions of and assumptions about assimilation, as well as choices about and interpretations of our data, to foster transparency and facilitate scholarly discovery. I conclude by arguing that scholars working in new immigrant destinations are well poised to examine how legal status - a key structural feature of the context of reception in a host society or locale - shapes assimilation processes and outcomes. © 2013 by the American Academy of Arts & Sciences.